Response Surface Methodology Based Optimized Purification of the Residual Glycerol from Biodiesel Production Process - Muhammad Danish (Science Faculty of Chiang Mai University, 2019)
Biodiesel is gaining acceptance as an alternative source of energy, due to its important properties, renewability, less toxicity and environmentally friendly attributes. One of the constrains, associated with the use of biodiesel as fuel is its high price. The most promising way to make it cost effective is the purification and utilization of its by-product glycerol. During the refining of glycerol, the following sequence was followed: acidification, neutralization, solvent extraction and decolorization. Optimized conditions for getting a high yield refined product were attained using the response surface methodology (RSM) for different parameters such as pH 1; extraction temperature, 50 °C; extraction time, 40 min; activated carbon dose, 2.0 g and rate of shaking, 350 rpm. Furthermore, the refined glycerol was characterized such as density, 1.65g/cm3; specific gravity, 1.23; ash content, 1.06; refractive index, 1.05 and pH, 6.05. Raman and FTIR spectroscopic methods were used for the monitoring of glycerol purification.